Analysis of the Needs of Relatives of Patients in Emergency Section of Zanjan Education-Medication Centers in 2019 - Samira Adineh Menbar; Nasrin Hanifi; Soheila Rabie Siahkali (Zanjan University of Medical Sciences and Health Services, 2019)
Background: Following hospitalization in various wards of a hospital, especially in the fully intensive wards of a hospital like emergency department, a patient's family and relatives start to face new needs which if are not considered, a crisis will erupt. Objectives: The goal of this research was to analyze the needs of the relatives of the patients hospitalized in the emergency department of the education and medication centers of the city of Zanjan in 2019. Methods: This descriptive study was done on the availibility sampling method in Poisson Point Distribution. The target population were 323 relatives of the patients in the emergency departments of the education and medication centers of the city of Zanjan. The instruments used for collection of the data was Critical Care Family Needs Inventory for Emergency Departments (CCFNIED). Results: Results showed that in opinion of families, the needs in terms of importance were as follows: The communication needs (3.67 ± 0.30), the participation needs (3.41 ± 0.39), supportive needs (3.13 ± 0.40), and finally the welfare needs (3.05 ± 0.39). Conclusion: The communication need was the most important need of families. Regarding importance of the health of family in patient's recovery, identification of the needs of the family of the patients should be part of nursing care and their elimination in the emergency and other wards of the hospital is recommended.